Phytochemical Studies on Medicinal Plants, Dracaenaceae resin, of Socotra Island, Yemen - Al- Mahweety, Jamal A. N. (PSM Biological Research, 2016)
Phytochemical study on the resin of Dracaenaceae obtained from Socotra Island has been conducted. The separations of the chemical components were carried out by different chromatography techniques and their structures were elucidated by spectroscopic methods such as mass spectrometry (MS), 1H and 13C NMR and by comparison with those of previously reported data. Four compounds were isolated and identified as follows, one triterpenes was isolated which was identified as Stigmasterol and two were flavonoides which were identified as Pentahydroxy flavanone and Dracophaney, and fourth one identified as Orobol.